The transvaginal mesh decade. (September 2013) - Maher, Christopher; Haya, Nir
During the transvaginal mesh era some women have suffered unexpectedly poor outcomes following the insertion of transvaginal mesh for the surgical management of pelvic organ prolapse. To minimize the risk of these events repeating, we support changes to approval process of new devices including premarket demonstration of safety and efficacy. Clinicians should demonstrate greater vigilance in the introductory phase of new technologies including incorporating ethics committee approval for procedures without adequate safety and efficacy data. Formalization of an 'arm's length' relationship between clinicians and industry would help minimize conflicts of interest which may unduly bias the introduction of new technologies and create improved transparency and confidence. Colleges and educational societies where the elected representatives are free of any relationship with industry could facilitate the 'arm's length' relationship between clinician and industry that our community demands. These changes to regulatory approval, caution in the introduction of new technologies and greater transparency surrounding the relationship between industry and clinicians should minimize the risk of patients suffering significant unforeseen complications and poor outcomes.